ASSESSMENT OF PHARMACOLOGICAL INTERVENTIONS AND COPING STRATEGIES FOR MANAGEMENT OF INSOMNIA: A SURVEY-BASED STUDY AMONG MEDICAL PRACTITIONERS AND THE PATIENTS WITH INSOMNIA - Sawaira Ghaffar; Alina Junaid; Zubia Fatima Mirza; Mahrukh Safeer; Umaima Athar Khan; Muhammad Ali; Rabia Noor; Uroosa Kanwal; Noor Kamil; Sana Ejaz (International Journal of Pharmacy & Integrated Health Sciences, 2025)
Background: Insomnia is a common sleep problem that profoundly impacts health and quality of life globally, influencing everyday functioning and mental well-being. Objectives: The study aims to assess the effectiveness of pharmacological interventions and coping strategies for managing insomnia. Methodology: A cross-sectional, online survey-based study was conducted with 238 participants, comprising 196 non-practitioners (NPs) and 42 medical practitioners (MPs). Statistical analyses evaluated relationships between insomnia awareness, prescribed medications, and demographic factors. Results: The study revealed that 30.43% of individuals with secondary education and 16.67% of those with a bachelor's degree were unfamiliar with the term insomnia. A significant relationship was observed between MPs encountering insomnia patients and the most effective medications they prescribe regarding patient satisfaction (p = 0.021). The relationship between MP types and their medicines for managing insomnia was significant (p = 0.058). The statistical association between participants' gender and the sleep issues they experienced was one of the study's significant findings (p = 0.019 and 0.012). Participants of all ages, genders, and socioeconomic groups knew "insomnia" (p = 0.04, 0.000, and 0.024). Conclusion: This study concluded the significance of a comprehensive and individualized approach to insomnia treatment. It also pointed out that more awareness, proactive screening, and a balanced approach to both psychological and prescription drug therapies are required.